Some special Problems of Soil Conservation Extension - Singh, Y P (Journal of Soil and Water Conservation, 2022)
Out of total cultivated area in the country about 140 million acres are affected by soil erosion in vary- ing degrees. Of these some 100 mil- lion acres are in advanced stage of deterioration that need prompt ac- tion. In addition there are about 50 million acres of fallow and other uncultivated land which arc badly eroded and are endangering our economic life. In the third plan it is expected to protect about ] 6 million acres by various conser- vation measures. I How can this serious problcrn be tackled ? Except, perhaps thc large scale afforestation and refore- station work and . major engineer- ing projects, which can be executed departmentally many other soil conservation programme will have to be executed by farmers themselv- es2. The soil must be conserved ultimately by those who till the land and live by its products3. This fact is fully appreciated in India to-day and large scale soil conser- vation extension work is underway. Soil conservation extension work however, poses some special diffi. cullies, besides the normal prob. lems met with any kind of exten. Sion work. The aim of the present paper is to indicate some diffcul. tics that arise in connection with the content of communication of soil conservation extension programme.